Civil Society 5.0 within the Global Sustainable Development Goals (SDGs) Paradigm: An Islamic Da'wah Perspective - Siti Nuri Nurhaidah; Retno Kartini Savitaningrum; Siti Atieqoh; Dewi Nurani; Evalinda (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The Sustainable Development Goals (SDGs) face serious challenges as the 2030 deadline approaches, with many targets experiencing stagnation and even regression across various sectors of global development. On the other hand, the world is entering the era of Society 5.0, which integrates cyberspace and physical space to balance economic progress with innovative and sustainable solutions to social problems. This article aims to analyze the integration of the Civil Society 5.0 concept with the SDGs paradigm through the perspective of Islamic da’wah based on Maqasid al-Shariah as an ethical-operational framework. This study employs a qualitative method with a conceptual literature review approach, examining UN documents, national regulations, as well as contemporary tafsir and fiqh literature. The findings indicate that the principles of khalifah fil ardh, mizan, and the five pillars of Maqasid al-Shariah are aligned with the 17 SDGs and provide a strong moral foundation for sustainable development. Concrete implementations include technology-based zakat optimization, halalan tayyiban food education, psycho-spiritual health integration, and inclusive education grounded in gender justice. However, challenges remain, including the commodification of religion, the digital divide, and epistemological limitations. Islamic da’wah plays a catalytic role in advancing a sustainable digital civil society